Quality Improvement in Higher Education – Role of Indicators and Student Feedbacks in Course Improvement - Bedzsula, Bálint (International Journal of Engineering and Management Sciences, 2016)
Customer oriented conduct and process-based thinking have become quasivital pillars of durable competitiveness for the business world today. Following this approach should result in satisfied customers, decreased costs, and efficient employees. However, the actors in higher education are just starting tolerant his way of thinking. The increasing focus on quality issues and the process-related approach to this is catalyzed by several factors. These concept is not a new issue at the Budapest University of Technology and Economics. The Department of Management and Corporate Economics as the flagship of teaching and researching quality management at the University looks for opportunities to give practical answer. Based on this the purpose of my paper is to demonstrate different examples at the different level of processes in higher education.